2005
DOI: 10.7901/2169-3358-2005-1-453
|View full text |Cite
|
Sign up to set email alerts
|

Net Environmental Benefit Analysis (Neba) of Dispersed Oil on Nearshore Tropical Ecosystems Derived From the 20 Year “Tropics” Field Study1

Abstract: In November 1984, non-treated Prudhoe Bay crude oil and dispersed Prudhoe Bay crude oil were intentionally released into two separate sites, representative of near shore mangrove, seagrass and coral ecosystems, as part of the TRopical Oil Pollution Investigations in Coastal Systems (TROPICS) field study in Bahia de Almirante, Panama. Data on the relative effects of non-treated crude oil and dispersed crude oil on these ecosystems (compared to a reference site) were acquired and analyzed over various periods (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Spongiosis hepatis, consisting of spaces filled with pale eosinophilic material as observed in the present study, has been reported in fish exposed to chemicals in the laboratory and fish from contaminated regions (Lauren, Teh, and Hinton 1990;Couch 1991;Balch et al 1995). These lesions may co-occur with hepatic neoplasms in wild fish (Metcalfe 1998) and provide an excellent example of histopathological biomarker for contaminant exposure (Hinton et al 1992).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Spongiosis hepatis, consisting of spaces filled with pale eosinophilic material as observed in the present study, has been reported in fish exposed to chemicals in the laboratory and fish from contaminated regions (Lauren, Teh, and Hinton 1990;Couch 1991;Balch et al 1995). These lesions may co-occur with hepatic neoplasms in wild fish (Metcalfe 1998) and provide an excellent example of histopathological biomarker for contaminant exposure (Hinton et al 1992).…”
Section: Discussionsupporting
confidence: 77%
“…Baca et al (2005) showed that applying dispersant increases the exposure to total polyaromatic hydrocarbons for pelagic organisms living in the water column, but it decreases the exposure to polyaromatic hydrocarbons for benthic organisms. Embryo-larval and early juvenile life stages are generally most sensitive to chemicals (George-Ares and Clark 2000).…”
Section: Discussionmentioning
confidence: 99%
“…When extrapolated to field operations in the shallow water of nearshore areas, the 431 results show that the application of dispersants would promote higher concentrations of TPH 432 in the water column but would decrease the adherence to substrates (seagrass beds, sediments 433 etc…). This result is in accordance with Baca et al (2005) and shows that dispersant 434 application increases the exposure to TPH for pelagic organisms living in the water column 435 (as golden grey mullets), while decreases the exposure to TPH for benthic organisms. With regards to the 16 USEPA PAHs (alkylated and parent), the results show that light PAHs 453 (two to three rings) were predominant in the WSF, CD and MD exposure media at T=0 h and 454 19 T=48 h. This observation is consistent with the current theory that the aqueous solubility 455 increases as the molecular weight of PAHs decreases (Neff, 1979) Ramachandran et al (2004) showed that oil dispersant increases PAHs uptake by fish exposed 486 to crude oil.…”
Section: Introduction 55 56supporting
confidence: 82%
“…This restriction of minimum water depths was 64 derived from studies on the dilution of dispersed oil in shallow water and took into 65 consideration the ecological sensitivity of nearshore areas as they are nurseries for many 66 aquatic species. However, a field study conducted by Baca et al (2005) suggests that, in 67 nearshore tropical ecosystems, dispersant use minimizes the environmental damages arising 68 from an oil spill. This Net Environmental Benefits Analysis (NEBA) highlights a positive 69 environmental role of dispersant use in nearshore areas but it is only applicable to tropical 70 mangroves.…”
Section: Introduction 55 56mentioning
confidence: 99%
“…An important finding of that study was that, compared with the chemically dispersed treatment, physically dispersed oil caused greater shoreline and intertidal oiling and related toxic impacts [15]. Although other field studies have provided useful assessments of dispersant used in oil spill response and characterized the environmental fate of the oil, and in some cases characterized impacts on biota [1,4,16,17], they have not provided sufficiently detailed exposure-response data to allow for direct comparisons with laboratory toxicity test data.…”
Section: Issues and Challenges With Oil Toxicity Datamentioning
confidence: 99%